Congenital transmandibular dermoid: case report - O. Koshy,* L. Ion, N. Waterhouse (Blackwell Synergy, 2000)
Congenital dermoids arise as result of epidermal sequestration during development and are quite common along the lines of fusion. While submandibular dermoids are common, we could find only a few references to dermoid cysts embedded in the mandibular bone itself and we describe one such case.